MIRROR THERAPY MENINGKATKAN KEKUATAN OTOT PASIEN PASCA STROKE NON HEMORAGIK DENGAN HEMIPARASE - arif, ahmad zaini; Jatimi, Atika; Adimah, Adimah; Istibsaroh, Faridatul (NHM PRESS, 2024)
Backround Stroke is a disease that can attack, paralyze and kill humans. A person with a stroke has functional brain disorders such as nerve paralysis (Neurologic Deficit) which is often experienced by stroke patients. One of the impacts that occurs in stroke sufferers is weakness on the other side of the body affected by the stroke/Hemiparase. Objective: The aim of this research is to analyze the effect of Mirror Therapy and mirror therapy on muscle strength in non- hemorrhagic post-stroke patients with Hemiparase. Method: This study used a Quasy experimental design using a pre post test control group design approach. The sample size in this study consisted of 2 groups, namely treatment and control with a simple random sampling technique, totaling 19 post-stroke patients each. Result: The results of the study showed that the difference in muscle strength between the treatment group was the average value ± standard deviation =1.95 ± (780) and the control group, namely the average value ± standard deviation = 1.37 ± (597). Based on the results of the Mann Whitney test with a value of (p=<0.016). This means that Mirror Therapy has an effect on increasing muscle strength in non-hemorrhagic post-stroke patients with hemiparase. Conclusion:Mirror Therapy can be an alternative therapy to drug therapy in increasing muscle strength in non- hemorrhagic post-stroke patients with hemiparase.